Prospective study of vocal fold function after loss of the neuromonitoring signal in thyroid surgery: The International Neural Monitoring Study Group's POLT study. (15th December 2015) - Schneider, Rick; Randolph, Gregory; Dionigi, Gianlorenzo; Barczyński, Marcin; Chiang, Feng‐Yu; Triponez, Frédéric; Vamvakidis, Kyriakos; Brauckhoff, Katrin; Musholt, Thomas J.; Almquist, Martin; Innaro, Nadia; Jimenez‐Garcia, Antonio; et al.
Abstract : Objectives/Hypothesis: Intraoperative neuromonitoring identifies recurrent laryngeal nerve (RLN) injury and gives prognostic information regarding postoperative glottic function. Loss of the neuromonitoring signal (LOS) signifies segmental type 1 or global type 2 RLN injury. This study aimed at identifying risk factors for RLN injury and determining vocal fold (VF) function initially and 6 months after definitive LOS. Study Design: Prospective study encompassing 21 hospitals from 13 countries. Methods: Included in this study were patients with persistent intraoperative LOS. Results: At first postoperative laryngoscopy, early VF palsy was present in 94 of all 115 patients with LOS (81.7%): in 53 of 56 patients (94.6%) with type 1 injury and 41 of 59 patients (69.5%) with type 2 injury. In LOS type 1, women outnumbered men >5‐fold. Traction produced LOS type 1 in 38 of 56 patients (67.9%) and LOS type 2 in 54 of 59 patients (91.5%). Course of the RLN posterior and/or anterior to the inferior thyroid artery, extralaryngeal branching, or tuberculum of Zuckerkandl did not increase VF palsy rates. Permanent VF palsy rates were also lower ( P = .661) after LOS type 2 than after LOS type 1: 6.8% (four of 59 patients) versus 10.7% (six of 56 patients). Intraoperative administration of steroids did not diminish postoperative VF palsy rates. Conclusions: LOS type 1 entails more severe nerve damage than LOS type 2, affecting women disproportionately. Both LOS types, being primarily associated with traction injury, are unaffected by variant neck anatomy in expert hands and unresponsive to steroids. Level of Evidence: 2b Laryngoscope, 126:1260–1266, 2016